Back Cover: Selective placement of quantum dots on nanoscale areas of metal‐free substrates (Phys. Status Solidi RRL 8/2014). Issue 8 (August 2014) - Staude, Isabelle; Sreenivasan, Varun K. A.; Shishkin, Ivan; Samusev, Kirill; Decker, Manuel; Neshev, Dragomir N.; Zvyagin, Andrei V.; Kivshar, Yuri S.
<x xml:space="preserve">Abstract</x> No Abstract